2016
DOI: 10.4172/2472-0992.1000124
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Antimicrobial Potential of Honey Samples from Apis mellifera and Two Stingless Bees from Nsukka, Nigeria

Abstract: The antimicrobial activity of honey depends on many factors, including its botanical origin, geographical and entomological source. The aim of this study was to evaluate and compare the antimicrobial potential of honey varieties from Apis mellifera, Hypotrigona sp. and Melipona sp. against MDR Staphylococcus aureus, Bacillus cereus, Escherichia coli, Pseudomonas aeruginosa ATCC 25783, Candida tropicalis, Candida albicans SC 5314 and Cryptococcus neoformans. By using standard microbiological procedure, the agar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…The different concentrations of the two honey samples had good growth inhibitory effect on the tested microorganisms. A similar result was previously reported by Mohapatra et al 47 for E. coli and P. aeruginosa 48 , for E. coli, K. pneumoniae and for Haemophilus influenza 49 . The less inhibition effect of the two tested honey against K. pneumoniae and S. aureus was in agreement with Patricia et al, 50 who reported that the overall poor activity of the honey against S. aureus was unexpected as previous reports which recorded that Maunka honey has an excellent activity against this organism.…”
Section: Resultssupporting
confidence: 90%
“…The different concentrations of the two honey samples had good growth inhibitory effect on the tested microorganisms. A similar result was previously reported by Mohapatra et al 47 for E. coli and P. aeruginosa 48 , for E. coli, K. pneumoniae and for Haemophilus influenza 49 . The less inhibition effect of the two tested honey against K. pneumoniae and S. aureus was in agreement with Patricia et al, 50 who reported that the overall poor activity of the honey against S. aureus was unexpected as previous reports which recorded that Maunka honey has an excellent activity against this organism.…”
Section: Resultssupporting
confidence: 90%
“…The epididymis was suggested to be an early target of lipid-related infertility and can be dramatically affected by excess intake of a high cholesterol diet (Ouvrier et al, 2011). On the other hand, the interest has been increased towards the use of honey as a prophylactic and therapeutic agent for various diseases as well as for improving and maintaining the overall wellbeing (Inoue et al, 2005;Nweze et al, 2016;Pyrzynska & Biesaga, 2009). Trihoney is a mixture of three types of honey namely Trigona, Mellifera and Tualang at a specific ratio.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, honey has proven to be an effective antimicrobial activity against both pathogenic and nonpathogenic microorganisms (such as bacteria, yeasts, and fungi), even in opposition to those microorganisms which have developed resistance to many antibiotics. The honey's antimicrobial effect could be bacteriostatic or bactericidal, relying upon the concentration used [4,11]. Notwithstanding, its potentials have been credited to specific variables like high osmolarity (low water action), low pH (acidity), hydrogen peroxide (H 2 O 2 ), and non-peroxide components [12,13].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…These unfastened radicals are initiated by specific leucocytes that are stimulated as major aspect of the inflammatory process, as inflammatory processes are what activate the series of cellular events which precipitate to the initiation of growth factors that influence proliferation of fibroblasts, angiogenesis, and epithelial cells [21]. Several honey types from different countries have been reported to have anti-inflammatory effect, including honeys from stingless bees [4].…”
Section: Anti-inflammatory and Immunomodulatory Activitiesmentioning
confidence: 99%
See 1 more Smart Citation